Using expectancy theory to examine occupational future time perspective with safety motivation and safety performance - Hanscom, Madison E., author; Cleveland, Jeanette, advisor; Gibbons, Alyssa, committee member; Murphy, Kevin, committee member; Shore, Lynn, committee member; Prince, Mark, committee member (Colorado State University. Libraries, 2020)
By better understanding employee safety motivation, organizations have the potential to reduce work-related accidents and injuries by improving motivation and safety behaviors. In the present study, the construct domain of safety motivation is expanded through the theoretical lens of expectancy theory by utilizing three components of safety motivation (i.e., valence of safety outcomes, instrumentality of safety outcomes, and expectancy) in addition to the most commonly utilized facet of safety motivation (i.e., safety importance). When these motivational facets were examined with three types of safety performance in the same model, results showed different relationships depending upon the safety performance outcome. The two motivational facets that showed the strongest relationships with safety compliance were both safety expectancy and safety importance. Safety expectancy was the strongest predictor of both safety participation and safety initiative. These findings indicate that expectancy theory can be applied within the safety space to explain the utility of safety motivation in predicting multiple types of safety performance. In a separate model, intrinsic and extrinsic components of valence and instrumentality were also examined, illustrating differential relationships with safety performance when these constructs are considered separately. As the age of the workforce increases, it is also important to understand how perceived time horizon might be associated with safety motivation and safety performance. In the present study, occupational future time perspective (OFTP; defined as a worker's perception of their remaining time and perceived opportunities left in their career) was examined as potential predictors of the multifaceted view of safety motivation. Results indicated as an individual's perceived opportunities at work increases, this was associated with an increase in all facets of safety motivation and performance; however, as one's remaining time increases at work, this was associated with weak negative relationships or no significant relationship with safety motivation. These results are discussed in relation to previous research and theory.
Keywords: occupational safety; safety climate; safety performance; safety behavior; occupational future time perspective; safety motivation